Estrategias socioafectivas y el rol docente - Acurio Diaz, María Fernanda (2023)
This research project aims to demonstrate the efficiency of socio-affective strategies in improving the teaching role and generating significant learning in the "General Quisquis" Educational Unit. It seeks to overcome the weaknesses found such as the lack of knowledge and experience for the development of strategies, skills, and socio-affective abilities in the teaching-learning process. The research used a qualitative-quantitative approach through the survey which was applied to the students of the fourth grade of basic education the data has been processed, interpreted, graphed and analyzed, which is used for the collection of information and construction of the theoretical framework in addition to interviews with the director, teachers and parents of the institution. The outcomes allowed us to show that socio-affective tactics that facilitate knowledge production must be used if motivation and self-esteem are to be preserved. Finally, it established norms for harmonious coexistence have been established, which seek to provide a safe and stimulating environment for all members of the educational community. Through a solid base of values and principles, we aspire to build a culture that promotes diversity, inclusion, and tolerance. To successfully establish a climate of cooperation and respect necessary for peaceful and harmonious coexistence, the implementation and validation of the suggested standards calls on the commitment and involvement of the entire educational unit.